Acceptable Wait Time Models at Transit Bus Stops - Arhin, S. A.; Gatiba, A.; Anderson, M.; Manandhar, B.; Ribbisso, M. (Engineering, Technology & Applied Science Research, 2019)
This study aimed at determining patrons’ acceptable wait times beyond the bus scheduled arrival time at bus stops in Washington, DC and to develop accompanying prediction models to provide decision-makers with additional tools to improve patronage. The research primarily relied on a combination of manual and video-based data collection efforts. Manual field data collection was used for surveying patrons to obtain their suggested acceptable wait times at bus stops, while video-based data collection was used to obtain bus stop characteristics and operations. In all, 3,388 bus patrons at 71 selected bus stops were surveyed. Also, operational data for 2,070 bus arrival events on 226 routes were extracted via video playback. Data were collected for AM peak, PM peak and mid-day periods of nine-month duration from May 2018 through January 2019. The results of the survey showed that the minimum acceptable wait time beyond the scheduled arrival time was reported to be 1 minute, while the maximum acceptable wait time was reported to be 20 minutes. Regression analyses were conducted to develop models to predict the maximum acceptable wait time based on factors including temperature, presence of shelter at the bus stops, average headway of buses, and patrons’ knowledge of bus arrival times. The models were developed for A.M., P.M. and mid-day periods. The F-Statistics for the models were determined to be statistically significant with p values